Internal limiting membrane translocation for refractory macular holes. Issue 3 (4th May 2016) - Pires, Joana; Nadal, Jeroni; Gomes, Nuno Lourenço
Abstract : Background/aims: Closure is more difficult to achieve in macular holes that remain open following a previous unsuccessful pars plana vitrectomy (PPV). We present our results with the internal limiting membrane (ILM) translocation technique that is used to optimise outcomes in refractory macular holes. Methods: A prospective, interventional, case series was conducted. 12 eyes of 12 consecutive patients with incomplete sealing of the macular hole (open and type 2 closure) after a previous PPV with ILM peeling were included. Measured baseline parameters included best-corrected visual acuity (BCVA) and macular hole smallest diameter, base diameter and height. Surgeries were performed by harvesting a fragment of the ILM near the vascular arcades and subsequently placing it inside the hole. Postoperative measured outcomes included macular hole status, foveal contour, outer retina integrity, BCVA and surgery-related complications. Results: Anatomic closure occurred in 11 of 12 eyes (91%). This technique elicited a statistically significant improvement in BCVA (p=0.008). Mean BCVA was 20/400 at study baseline and 20/160 at final follow-up. However, less than 16.7% of cases had a final BCVA of ≥20/63. Conclusion: The ILM translocation technique seems to facilitate persistent idiopathic macular hole closure, where primary surgery with PPV and ILM peeling failed.